2016
DOI: 10.1016/j.ebiom.2016.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Imaging Reveals Elevated Glomerular ATP/AMP in Diabetes/obesity and Identifies Sphingomyelin as a Possible Mediator

Abstract: AMP-activated protein kinase (AMPK) is suppressed in diabetes and may be due to a high ATP/AMP ratio, however the quantitation of nucleotides in vivo has been extremely difficult. Via matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) to localize renal nucleotides we found that the diabetic kidney had a significant increase in glomerular ATP/AMP ratio. Untargeted MALDI-MSI analysis revealed that a specific sphingomyelin species (SM(d18:1/16:0)) accumulated in the glomeruli of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 42 publications
7
90
0
Order By: Relevance
“…In addition, in murine mesangial cells, we found that SM (d18:1/16:0) suppressed AMPK activity and reduced PGC-1α protein expression. 33 The liposomal SM (d18:1/16:0) treatment significantly increased lactate secretion in murine mesangial cells, suggesting that accumulation of SM and an increase in ATP in the diabetic kidney may be owing to the result of an increase in glycolysis. This was proved further by the treatment of glycolytic inhibitor 2-deoxy-D-glucose, which significantly inhibited ATP production, suggesting the potential role of SM (d18:1/16:0) in enhancing the glycolytic pathway to enhance ATP production and thus contribute to a Warburg type effect in glomeruli of the diabetic kidney (Fig.…”
Section: Sphingomyelin: a Novel Mediator For Enhanced Atp Production mentioning
confidence: 96%
See 3 more Smart Citations
“…In addition, in murine mesangial cells, we found that SM (d18:1/16:0) suppressed AMPK activity and reduced PGC-1α protein expression. 33 The liposomal SM (d18:1/16:0) treatment significantly increased lactate secretion in murine mesangial cells, suggesting that accumulation of SM and an increase in ATP in the diabetic kidney may be owing to the result of an increase in glycolysis. This was proved further by the treatment of glycolytic inhibitor 2-deoxy-D-glucose, which significantly inhibited ATP production, suggesting the potential role of SM (d18:1/16:0) in enhancing the glycolytic pathway to enhance ATP production and thus contribute to a Warburg type effect in glomeruli of the diabetic kidney (Fig.…”
Section: Sphingomyelin: a Novel Mediator For Enhanced Atp Production mentioning
confidence: 96%
“…The hypothesis of an enhanced glycolytic pathway in diabetes was supported by recent studies from our laboratory using mass spectrometry imaging (MSI)-based spatial metabolomics in DKD animal models and human kidney tissue. 33 We applied matrix-assisted laser desorption/ionization (MALDI)-MSI to localize and quantify renal nucleotides. 33 MALDI-MSI at 70-µmol/L resolution identified ATP, adenosine diphosphate, and AMP widely distributed throughout the kidney and showed a significant increase in ATP and decrease in AMP, leading to significantly increased ATP/AMP in glomeruli of diabetic mice when compared with nondiabetic ones.…”
Section: Sphingomyelin: a Novel Mediator For Enhanced Atp Production mentioning
confidence: 99%
See 2 more Smart Citations
“…81 Some of these include the study of anticancer drug distributions in mouse kidneys, 82 glomerular adenosine triphosphateadenosine monophosphate ratios in diabetic mouse models, 83 N -linked glycans in murine kidneys, 84 murine tubular lipid distributions in immunoglobulin A nephropathy, 85 region-specific sphingolipid metabolism in murine models of obesity, 86 sulfatide turnover in animal models of lipid storage disease, 87 sulfated lipid markers in polycystic kidney disease rats, 88 renal angiotensin metabolism in mice, 89 peptide classification and pathogenesis of amyloidosis in humans, 90 racial disparities in Wilms tumor incidence and human peptide biology, 91 rat protein biomarkers of gentamicin nephrotoxicity, 92 and assessing proteomic patterns of glomerulosclerosis for disease classification and prosclerotic mechanism determination in rats. 93 While it is impractical to provide a detailed description of all IMS renal research in this review, several recent reports are described below that highlight discoveries in areas of clear cell renal cell carcinoma, diabetic nephropathy (DN), preclinical renal drug toxicology, and infectious disease.…”
Section: Maldi Imaging Mass Spectrometry: a Molecular Microscope For mentioning
confidence: 99%